Atrial fibrillation, anticoagulation and vitamins for homocysteine - Spence, J. David (Henry Stewart Talks, 2015)
Stroke, atrial fibrillation and aging population, Ischemic stroke subtypes, Role of anticoagulants and anti-platelets: data from clinical trials, New era in anticoagulation, Homocysteine and the risk for a cardiovascular event, Vitamin B12 deficiency and the risk for stroke: data from clinical trials